Influence of High Temperature on Different Plankton Ecology in the Future Ocean: Modeling Approach - Mimia, Mohima Sultana; Chowdhury, K M Azam; Moontahab, Ashraful; Khan, Tasin Sumaia; Hoquee, Mohammad Abrarul (BIMRAD Journal, 2026)
To accurately predict the responses of marine ecosystems to climate change, it is imperative to comprehend the interaction between increased carbon dioxide (CO2) levels and elevated temperatures and how it affects marine plankton ecology. However, there is a limited number of studies that have investigated the impacts of increased CO2 on marine plankton ecology. This study explores future ocean scenarios of global plankton dynamics under the influence of climate projections utilizing EcoGEnIE, a simplified Earth system model that couples biogeochemistry, ocean circulation, and climate processes to simulate long-term global environmental changes. A significant decline in total carbon biomass is observed worldwide, particularly at higher latitudes, with a pronounced reduction in plankton biomass in the North Atlantic Ocean. Surprisingly, in the isolating phytoplankton experiments, an increase in plankton biomass is observed, contrasting with the coupled phytoplankton-zooplankton experiments. Surface alkalinity and dissolved inorganic carbon (DIC) patterns is also predicted to increase in the model projections of the future global ocean, particularly in the Atlantic Ocean. While sea surface temperature rises due to elevated CO2 emissions, phytoplankton play a role in mitigating the increase in alkalinity and DIC in the surface ocean. Examination of ocean circulation patterns, focusing on the weakened Atlantic Meridional Overturning Circulation, reveals a connection between plankton ecology and ocean circulation. Additional experiments suggest that if the CO2 emissions will further increase, the impact on plankton biomass will persist and intensify, particularly in the Atlantic Ocean. This study emphasizes the intricate connection between changes in the ocean biogeochemical cycles, induced by climatic stresses, and the ecological dynamics of global planktonic communities. BIMRAD Journal VOLUME 6, ISSUE 1, DEC 2025; PP-28-47